Percepción de la pérdida auditiva en trabajadores del sector de la construcción, ciudad Quito - Campos, Yolis Yajaira (2017)
Studies are limited on the behavior of workers against the occupational hazards to which they are exposed, which is why the study of these is a relevant factor at the time of risk prevention because it is not enough with preventive measures of technical origin and organizational, it is necessary to study the human factor and its reliability. The objective of the study was to know the perception of workers exposed to noise in the face of hearing loss and hearing protection. A cross - sectional descriptive study was carried out on 20 workers in the production area of the construction sector, exposed to a continuous daily noise level equivalent to or greater than 85 decibels (A) in their workday. The total number of workers perceived the damage generated by exposure to noise in their daily work as non-problematic, however, all workers were aware that exposure to loud noise can cause damage to their hearing. 85% of workers stated that it was important to wear hearing protectors when they had exposure to noise above the allowed limit to maintain their hearing. Workers said they can’t always decide when they need to change hearing protectors. The study showed that, although workers are aware of the effects caused by excessive noise and the importance of the use of hearing protectors, greater training in self-sufficiency is required for the use, maintenance and replacement of hearing protectors; As well as the provision of more ergonomic equipment.